Genital Ambiguity in a 46, XY individual : a Rare Case - Zata Yuda Amaniko; Yuad, Haviz (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction: Ambiguous genitalia/disorders of sexual development (DSD) is a disorder of sexual development that is atypical chromosomally, gonadally and anatomically, which is generally characterized by the presence of unclear external genitalia, which can cause biological, social and psychological problems in the patient. as well as family. Objective: To report a rare case of 46 XY disorders of sexual development. Case Report: A 20 years old patient was reported with complaints of primary amenorrhea, breasts that had not yet grown and genitals resembling male genitals. Through physical examination, fine hair appeared above the lips, acne, prominent thyroid cartilage, mammary tanner stage M1, and a structure resembling a penis on the genitalia. The patient was examined according to the algorithm for patients with DSD, namely an ultrasound examination with the result that no gonads were found, then the patient underwent a karyotyping examination with results of 46 XY. In the investigation, it revealed LH: 58.45 mIU/ml, FSH: 57.74 mIU/ml, testosterone: 228 ng/dl. Next, the patient is planned for further imaging examinations. Conclusions: DSD is genetically heterogeneous and careful assessment by a multidisciplinary team is essential to accurately diagnose DSD. Many forms of DSD go undiagnosed. It is important for physicians to have a clear decision-making pathway in evaluating patients with DSD Keywords: Disorders of Sexual Development, Ambiguous Genitalia, 46 XY